PENGEMBANGAN LKPD BERBASIS OPEN ENDED BERBANTUAN APLIKASI CANVA PADA SISWA KELAS XI SMK N 5 MERANGIN - Sri Wahyuni; Hidayati Rais; Hasmawati (Hira Institute, 2026)
Mathematics learning at SMK N 5 Merangin faces problems due to limited teaching materials and the use of lecture methods with textbooks, which makes students less active and results in learning outcomes that do not meet the classical mastery criteria. This study aims to develop an open-ended Student Worksheet (LKPD) assisted by Canva that meets the criteria of being valid, practical, and effective for the Grade XI function topic. The development model used was ADDIE, with the research subjects being Grade XI students. The research instruments included validation sheets, practicality questionnaires, student activity observation sheets, and learning outcome tests. Validation results from five validators, consisting of material, language, media experts, and practitioners, showed an average validity score of 4.43 (very valid). The practicality aspect, based on questionnaires, reached 88% (very practical). Meanwhile, the effectiveness aspect was reflected in student learning activities reaching 88.17% (very active) and learning mastery of 83.3%. Thus, it can be concluded that the Canva-assisted open-ended LKPD is valid, practical, and effective.